Basic arithmetic on financial literacy skills: A new learning outcome - Sagita, Laela; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Prahmana, Rully Charitas Indra (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
Multiplication is the most difficult basic arithmetic operation and has been documented since 1980. Another multiplication difficulty dealing with story problems, they tend to assume that multiplication produces a larger result and the other way for division. Several studies show basic mathematics as one of the cognitive factors that affect the financial literacy ability of each individual. This study used a qualitative descriptive analysis with the subject of three students from different schools and geographical locations. Basic mathematics as one of the cognitive factors that affect the financial literacy ability of each individual The introduction of cases such as ordering through online applications in learning mathematics may improve students' knowledge about activities related to finance. Individual context is important in personal financial management since the decision pertains to the fulfilment of personal needs.